Examining the Presidential Threshold in Law No. 7 of 2017 in terms of legal politics in Indonesia - Fathullah, Fathullah (JURNAL RUANG HUKUM, 2023)
It was originally proposed that the presidential threshold of 20% be used to support the presidential system. As stated in Article 6A paragraph (2) of the Constitution of the Republic of Indonesia, the constitutional design of the presidential threshold is an additional provision about arrangements on the requirements for the candidacy of the President and Vice President. Because political configuration is so crucial to the creation of legal products, political law presidential threshold policymaking occurs when there is political configuration. What is the history of the presidential threshold policy of 20%? is the first of two problem formulations in this study. Second, how does the presidential threshold of 20% in Law No. 7 of 2017 stand in terms of legal politics? Along with legal and intellectual techniques, the research takes a normative perspective. First, the study's findings show that Indonesia's presidential threshold was first established in Law Number 23 of 2003 concerning the General Election of the President and Vice President. From the 2004 Presidential Election to the 2019 Presidential Election, Indonesia's threshold provisions were the first to be put into practice, with the presidential threshold's amount changing. The legal politics of the presidential threshold have the traits of an authoritarian law, and the legal foundation has changed to Law Number 7 of 2017 concerning the Second General Election. This is so that the ruler can protect his or her political interest in keeping the ruling party in power. Because a presidential threshold with a percentage of up to 20% creates a divide in political rights or democratic rights between parties with majority votes and parties with minority votes, the legal politics of determining the presidential threshold runs counter to the principle of the purpose of an effective and proportional election.